Effect of 100% human milk-derived fortifier on growth of premature infants with birth weight of 1000–1500 g - Pejaver, Ranjan Kumar; Maneesha, P H; Lingaraju, Subbanna (Indian Journal of Child Health, 2020)
Background: Preterm birth has the highest risk of perinatal morbidity and mortality. Nutrition plays a key role in the growth and development of a preterm infant. Fortification of expressed breast milk is followed to provide an optimal nutrition and a faster catch up growth. The new 100% human milk-derived fortifier (HMDF) can help in providing a safe nutritional option for a premature infant. Objective: The objective of the study was to assess the feed tolerance and impact of a new 100% HMDF on growth outcomes of preterm infants. Materials and Methods: In a single-center study, exclusively human milk-fed preterm infants (1000–1500 g birth weight) were chosen to receive human milk fortified with a new 100% HMDF. The fortifier was initiated when the enteral feed volume reached 100 ml/kg/day and was administered until discharge. The primary outcome of the study was to assess feed tolerance and the secondary endpoints included growth parameters. Results: The cohort study comprised 13 infants with a mean gestational age of 31.64±2.2 weeks and birth weight of 1314.62±110.1 g. During the study period, feed interruptions were nil and none of the infants showed any adverse events of clinical significance. Growth outcomes recorded at the end of the study period showed a mean weight gain of 25.97±7.7 g/day, mean length gain of 0.32±0.23 cm/week, and mean head circumference gain of 0.39±0.20 cm/week. The mean weight growth velocity of the infants was 18.37±5.1 g/kg/day. Conclusion: Preterm infants who received a new 100% HMDF demonstrated feed tolerance and weight gain without any clinically significant record of adverse events. The findings indicate that the new HMDF is a safe option for providing an exclusive human milk-based diet. However, a study with a larger study population may be required to reinforce the findings of this study.